Altered microtubule structure, hemichannel localization and beating activity in cardiomyocytes expressing pathologic nuclear lamin A/C. Issue 1 (January 2020) - Borin, Daniele; Peña, Brisa; Chen, Suet Nee; Long, Carlin S.; Taylor, Matthew R.G.; Mestroni, Luisa; Sbaizero, Orfeo
Abstract: Given the clinical effect of laminopathies, understanding lamin mechanical properties will benefit the treatment of heart failure. Here we report a mechano-dynamic study of LMNA mutations in neonatal rat ventricular myocytes (NRVM) using single cell spectroscopy with Atomic Force Microscopy (AFM) and measured changes in beating force, frequency and contractile amplitude of selected mutant-expressing cells within cell clusters. Furthermore, since beat-to-beat variations can provide clues on the origin of arrhythmias, we analyzed the beating rate variability using a time-domain method which provides a Poincaré plot. Data were further correlated to cell phenotypes. Immunofluorescence and calcium imaging analysis showed that mutant lamin changed NRVMs beating force and frequency. Additionally, we noted an altered microtubule network organization with shorter filament length, and defective hemichannel membrane localization (Connexin 43). These data highlight the interconnection between nucleoskeleton, cytoskeleton and sarcolemmal structures, and the transcellular consequences of mutant lamin protein in the pathogenesis of the cardiac laminopathies . Abstract : Biological sciences; Cardiology; Biomechanics; Cytoskeleton; Mechanical property; Membrane; Lamin A/C; Cardiomyopathy; Atomic force microscopy; Cardiomyocytes; Beating; Cx43